Mechanical Performance of Amorphous Diamond-Like Carbon Nanowires - Allende-Prieto, S (Elsevier Ltd, 2024)
Amorphous carbon nanowires (NW) are a fundamental piece in the study of novel nanoarchitectures with unexpected mechanical properties. However, the failure mechanism of amorphous carbon NW is still missing. In this study, classical molecular dynamics was employed to conduct stress-strain tests to address the mechanical response of amorphous carbons NW with different radii. This research characterizes the mechanical properties of aC NW with different sp3 contents, including Youngs modulus and ultimate tensile stress. Our study reveals that plastic deformation is mediated by chemical modifications in carbon bonding, leading to transitions from sp2 to sp3 and vice versa. We observed that denser amorphous carbon materials undergo a transition from sp3 to sp2 bonding prior to failure, facilitated by the recombination of sp2 clusters. Additionally, plastic deformation in amorphous carbon NW is facilitated by the formation of shear transformation zones and nanovoids, with the deformation mechanism strongly dependent on the average coordination of carbon atoms. These insights provide valuable information for designing nanomaterials with tailored mechanical properties. © 2024 Elsevier B.V.